Realizing the ASEAN Economic Community: A Comprehensive Assessment - Tecson, Gwendolyn (Kasarinlan: Philippine Journal of Third World Studies; Vol 25 No 1-2 (2010): Political Economy of Ideas, 2010)
Review of Plummer, Michael G., and Chia Siow Yue, eds. 2009. Realizing the ASEAN Economic Community: A Comprehensive Assessment. Singapore: Institute of Southeast Asian Studies. 252 pp.